The complex communication signals in the mating behavior of the tropical cricket Cranistus colliurides Stål, 1861 (Orthoptera: Grylloidea; Trigonidiidae: Phylloscyrtini) - Centeno, Elliott; Zefa, Edison (Zootaxa, 2019)
Cricket mating behavior reflects different strategies developed by sexual selection throughout evolutionary time. To our knowledge, only one species of the Neotropical cricket Trigonidiinae had its mating behavior studied so far. Here we expand this knowledge by describing the mating behavior of Cranistus colliurides Stål, 1861, a cricket commonly found in bushes and grasses along open fields or the forest edge. Adult crickets were collected in the municipality of Capão do Leão, State of Rio Grande do Sul, Brazil. Trials were carried out in laboratory to characterize the mating sequence. We quantified elapsed time of each behavioral sequence and discussed its implications in the observed mating behavior. The males of C. colliurides attracted females by means of a continuous trill, and receptive female triggers the beginning of the courtship through antennation. During courtship, copulation and post-copulatory actions, males showed a complex communication system based on information send to female by substrate vibration and an elaborated repertoire composed by calling, courtship and post-copulatory song. The mating behavior here described reveals divergence between related species hitherto studied which give us clues to understand how the sexual selection shaped the complex behaviors exhibited by Trigonidiinae crickets presently.